THE INTEGRATION OF PODCAST-ASSISTED MEDIA AND PROJECT-BASED LEARNING TO ENHANCE ENGLISH SPEAKING SKILLS OF STUDENTS AT UNIVERSITAS MUHAMMADIYAH ENREKANG (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2025)
Podcasts have gained popularity as a flexible medium for delivering information across diverse genres, including news, entertainment, personal development, and education. This study investigates the integration of podcast-assisted media and Project-Based Learning (PjBL) to enhance English-speaking skills among third-semester students enrolled in the Public Speaking and Presentation course at Universitas Muhammadiyah Enrekang. The research addresses challenges in traditional language instruction, such as limited speaking opportunities and student anxiety, by leveraging the flexibility and authenticity of podcasts. Employing a pre-experimental one-group pretest-posttest design, the study examines the impact of this method on students' speaking abilities. Data analysis was conducted using a paired sample t-test, revealing a significant improvement in speaking skills, as indicated by the pretest and posttest score comparison (t = -34.997, p = 0.000). The findings demonstrate that integrating podcast-assisted media with Project-Based Learning (PjBL) provides an effective approach to enhancing students' English-speaking skill, offering opportunities for active participation and authentic listening experiences.